Kynurenine and Tetrahydrobiopterin Pathways Crosstalk in Pain Hypersensitivity - Staats Pires, Ananda; Tan, Vanessa X.; Heng, Benjamin; Guillemin, Gilles J.; Latini, Alexandra (Frontiers in Neuroscience, 2020)
Despite the identification of molecular mechanisms associated with pain persistence, no significant therapeutic improvements have been made. Advances in the understanding of the molecular mechanisms that induce pain hypersensitivity will allow the development of novel, effective and safe therapies for chronic pain. Various pro-inflammatory cytokines are known to be increased during chronic pain, leading to sustained inflammation in the peripheral and central nervous systems. The pro-inflammatory environment activates additional metabolic routes, including the kynurenine (KYN) and tetrahydrobiopterin (BH4) pathways, which generate bioactive soluble metabolites with the potential to modulate neuropathic and inflammatory pain sensitivity. Inflammation-induced up-regulation of indoleamine 2,3-dioxygenase 1 (IDO1) and guanosine triphosphate cyclohydrolase I (GTPCH), both rate-limiting enzymes of KYN and BH4 biosynthesis, respectively, have been identified in experimental chronic pain models as well in biological samples from patients affected by chronic pain. Inflammatory inducible KYN and BH4 pathways upregulation is characterized by increase in pronociceptive compounds, such as quinolinic acid (QUIN) and BH4, in addition to inflammatory mediators such as interferon gamma (IFN-γ) and tumour necrosis factor alpha (TNF-α). As expected, the pharmacologic and genetic experimental manipulation of both pathways confers analgesia. Many metabolic intermediates of these two pathways such as BH4, are known to sustain pain, while others, like xanthurenic acid (XA; a KYN pathway metabolite) have been recently shown to be an inhibitor of BH4 synthesis, opening a new avenue to treat chronic pain. This review will focus on the KYN/BH4 crosstalk in chronic pain and the potential modulation of these metabolic pathways that could induce analgesia without dependence or abuse liability.